Analysis of solidification of phase change material flowing through a channel with backward step: Effects of step curvature - Öztop, Hakan Fehmi; Kiyak, Burak; Biswas, Nirmalendu; Selimefendigil, Fatih; Cosanay, Hakan (Elsevier, 2024)
Thermal energy storage (TES) allows to the conservation of energy, enhancing the overall system efficiency and balancing the supply and demand of energy. This article presents a computational analysis of the solidification process of melted paraffin wax phase change material (PCM) through a partially heated backward-facing step channel partially cooled from the bottom and top. Melted PCM enters through the left opening of the step channel and leaves through the right opening. The study examines two distinct cases: considering sharp stepped or angular corner, and stepped or streamlined corner (of radius r = 20 mm) with the same inlet flow and boundary conditions. A comprehensive numerical model is developed and solved using the finite volume-based computational approach. The overall thermal performance of the model during the solidification process is evaluated for the different Reynolds numbers (Re = 20 and 40) and temperature differences (Delta T = 20 and 25 degrees C) for the different time steps. Furthermore, the effect of backward step curvature on the solidification process is also analyzed. The results revealed that all the parameters (Re, Delta T, and curvature) affect the melted PCM flow structure as well as the solidification process inside the channel. Changing the sharp step corner into a streamlined one at the bottom of the channel led to the lowest lesser flow separation and faster solidification process. Therefore, a well-designed streamlined step corner and its shape could be used to increase the discharging speed of thermal energy storage units meaningfully. Furthermore, such designs, the placement of the heater and cooler location, and step curvature are the guiding factors for controlling the performance of the energy storage. With the change in the curvature, the energy efficiency can be increased and the solidification time is lowered by at least 5 %.
Keywords: Phase change material (PCM); Solidification; Step-channel; Curvature; Heat transfer